THE EFFECT OF GREEN FINANCING INTENSITY ON FIRM VALUE IN BANKING: THE MEDIATING ROLE OF OPERATIONAL COST EFFICIENCY (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effect of Green Banking on firm value, with operational efficiency (BOPO) as a mediating variable in banking companies listed on the Indonesia Stock Exchange during the 2021–2025 period. Firm value is measured using Price to Book Value (PBV), Green Banking is proxied by the Green Financing Ratio, while operational efficiency is measured using BOPO (Operating Expenses to Operating Income). The sample consists of 29 banking companies with 145 bank-year observations. The data were analyzed using panel data regression and mediation analysis. The results show that Green Banking has a positive and significant effect on firm value, with a coefficient of 0.05092 and a probability value of 0.0016. Furthermore, Green Banking has a significant effect on operational efficiency, as measured by BOPO, with a coefficient of 0.36326 and a probability value of 0.0179. Operational efficiency, as measured by BOPO, also has a significant effect on firm value, with a coefficient of 0.03201 and a probability value of 0.0008. The mediation analysis indicates that the indirect effect of Green Banking on firm value through BOPO is 0.01163 and statistically significant at the 5% level (p = 0.0487). Since the direct effect of Green Banking on firm value remains significant after BOPO is included in the model, BOPO functions as a partial mediator. These findings indicate that the implementation of Green Banking is not only relevant from a sustainability perspective but also contributes to firm value creation through operational mechanisms. Therefore, banks should integrate sustainable financing practices with effective operational management to maximize the contribution of Green Banking to firm value.